2012
DOI: 10.1108/09615531211208060
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer from truncated cones with variable wall temperature and concentration in the presence of chemical reaction effects

Abstract: Purpose -The purpose of this paper is to solve the problem of steady, laminar, coupled heat and mass transfer by MHD natural convective boundary-layer flow over a permeable truncated cone with variable surface temperature and concentration in the presence of thermal radiation and chemical reaction effects. Design/methodology/approach -The governing equations are derived and transformed into a set of non-similar equations which are then solved by an adequate implicit finite difference method. Findings -It is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 26 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…Bergstrom [5] reported on the oscillating flow of rotating fluid problem in a boundary layer past a vast half-plate. Other earlier works include [6][7][8][9][10][11]. Waqas et al [12] reported on thermally developed Falkner-Skan bioconvection flow of a magnetized nanofluid in the presence of motile gyrotactic microorganism: Buongiorno's nanofluid model.…”
Section: Introductionmentioning
confidence: 99%
“…Bergstrom [5] reported on the oscillating flow of rotating fluid problem in a boundary layer past a vast half-plate. Other earlier works include [6][7][8][9][10][11]. Waqas et al [12] reported on thermally developed Falkner-Skan bioconvection flow of a magnetized nanofluid in the presence of motile gyrotactic microorganism: Buongiorno's nanofluid model.…”
Section: Introductionmentioning
confidence: 99%
“…Muthucumaraswamy et al (2013) have studied the effects of rotation and chemical reaction on the hydromagnetic freeconvection flow of a fluid past a uniformly accelerated infinite isothermal vertical plate with variable mass diffusion. Chamkha et al (2012) have analyzed the heat and mass transfer from truncated cones with variable wall temperature and concentration in the presence of chemical reaction effect.…”
Section: Introductionmentioning
confidence: 99%
“…The Hamilton and Crosser model [39] is used for the thermal conductivity of different shapes of CdTe nanoparticles. For validation purposes, some limited cases of the current study are compared with the numerical results provided in References [40,41], as shown in Table 4 and the results are in excellent agreement.…”
Section: Graphical Results and Discussionmentioning
confidence: 58%